Increasing Fruit Weight by Editing a Cis-Regulatory Element in Tomato KLUH Promoter Using CRISPR/Cas9 - Li, Qiang; Feng, Qian; Snouffer, Ashley; Zhang, Biyao; Rodríguez, Gustavo Rubén; van der Knaap, Esther (Frontiers in Plant Science, 2022)
CRISPR/Cas-mediated genome editing is a powerful approach to accelerate yield enhancement to feed growing populations. Most applications focus on ‘negative regulators’ by targeting coding regions and promoters to create nulls or weak loss-of-function alleles. However, many agriculturally important traits are conferred by gain-of-function alleles. Therefore, creating gain-of-function alleles for ‘positive regulators’ by CRISPR will be of great value for crop improvement. CYP78A family members are positive regulators of organ weight and size in crops. Here, we engineered allelic variation by editing tomato KLUH promoter around a SNP that is highly associated with fruit weight. The SNP was located in a conserved putative CRE as detected by homology-based prediction and ATAC-seq (assay for transposase-accessible chromatin using sequencing). Twenty-one mutant alleles with various insertion and deletion sizes were generated in the LA1589 background. Five mutant alleles (m2+4bp, m3+1bp, m5-1bp, m13-8bp and m14-9bp) showed a consistent increase in fruit weight and a significant decrease in the proportion of small fruits in all experimental evaluations. Notably, m2+4bp and m3+1bp homozygote significantly increase fruit weight by 10.7% ~ 15.7% and 8.7% ~16.3%, respectively. Further analysis of fruit weight based on fruit position on the inflorescence indicated that the five beneficial alleles increase the weight of all fruits along inflorescence. We also found that allele types and transcriptional changes of SlKLUH were poor predictors of the changes of fruit weight. This study not only provides a way of identifying conserved CRE but also highlights enormous potential for CRISPR/Cas-mediated cis-engineering of CYP78A members in yield improvement.